Answer:
6
Step-by-step explanation:
the rate of change is given by the slope of the line
the equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y-intercept )
f(x) = 6x - 5 is in this form
with slope m = 6 ← rate of change
7 inches = 49 cents
8 inches = 56 cents
11 inches = 77 cents
Answer: The measure in degrees of angle S is 33.7°
Step-by-step explanation: Please see the attachments below for the complete question as well as the Step-by-step explanation
We will turn the left side into the right side.
![\dfrac{1 + \cos 2x}{1 - \cos2x} = \cot^2 x](https://tex.z-dn.net/?f=%20%5Cdfrac%7B1%20%2B%20%5Ccos%202x%7D%7B1%20-%20%5Ccos2x%7D%20%3D%20%5Ccot%5E2%20x)
Use the identity:
![\cos 2x = \cos^2 x - \sin^2 x](https://tex.z-dn.net/?f=%20%5Ccos%202x%20%3D%20%5Ccos%5E2%20x%20-%20%5Csin%5E2%20x%20)
![\dfrac{1 + \cos^2 x - \sin^2 x}{1 - ( \cos^2 x - \sin^2 x)} = \cot^2 x](https://tex.z-dn.net/?f=%20%5Cdfrac%7B1%20%2B%20%5Ccos%5E2%20x%20-%20%5Csin%5E2%20x%7D%7B1%20-%20%28%20%5Ccos%5E2%20x%20-%20%5Csin%5E2%20x%29%7D%20%3D%20%5Ccot%5E2%20x)
![\dfrac{1 - \sin^2 x + \cos^2 x }{1 - \cos^2 x + \sin^2 x} = \cot^2 x](https://tex.z-dn.net/?f=%20%5Cdfrac%7B1%20-%20%5Csin%5E2%20x%20%2B%20%5Ccos%5E2%20x%20%7D%7B1%20-%20%5Ccos%5E2%20x%20%2B%20%5Csin%5E2%20x%7D%20%3D%20%5Ccot%5E2%20x)
Now use the identity
solved for sin^2 x and for cos^2 x.
![\dfrac{\cos^2 x + \cos^2 x }{\sin^2 x + \sin^2 x} = \cot^2 x](https://tex.z-dn.net/?f=%20%5Cdfrac%7B%5Ccos%5E2%20x%20%2B%20%5Ccos%5E2%20x%20%7D%7B%5Csin%5E2%20x%20%2B%20%5Csin%5E2%20x%7D%20%3D%20%5Ccot%5E2%20x%20)
![\dfrac{2\cos^2 x}{2\sin^2 x} = \cot^2 x](https://tex.z-dn.net/?f=%20%5Cdfrac%7B2%5Ccos%5E2%20x%7D%7B2%5Csin%5E2%20x%7D%20%3D%20%5Ccot%5E2%20x%20)
![\dfrac{\cos^2 x}{\sin^2 x} = \cot^2 x](https://tex.z-dn.net/?f=%20%5Cdfrac%7B%5Ccos%5E2%20x%7D%7B%5Csin%5E2%20x%7D%20%3D%20%5Ccot%5E2%20x)
![\cot^2 x = \cot^2 x](https://tex.z-dn.net/?f=%20%5Ccot%5E2%20x%20%3D%20%5Ccot%5E2%20x%20)
Answer:
y= 3x^2 y= 3^x
1. 3. 3
2. 12. 9
Step-by-step explanation:
3(1)^1
3
3^1
3
3(2)^2
3(4)
12
3^2
9